Unravelling the Role of Rhizosphere Microbiome and Root Traits in Organic Phosphorus Mobilization for Sustainable Phosphorus Fertilization. A Review - Amadou, Issifou; Houben, David; Faucon, Michel-Pierre (Agronomy (Basel), 2021)
Moving toward more sustainable sources for managing phosphorus (P) nutrition in agroecosystems, organic phosphorus (Po) derived from organic inputs and soil is increasingly considered to complement mineral P fertilizer. However, the dynamics of P added by organic input in soil-plant systems is still poorly understood and there is currently no clear information on how the Po composition of these amendments determines P availability through interactions with the soil microbiome and root traits. Here, we review the main mechanisms of rhizosphere microbiome and root traits governing the dynamics of organic input/soil-derived Po pools in the soil-plant system. We discuss the extent to which the major forms of Po derived from organic input/soil can be used by plants and how this could be improved to provide efficient utilization of organic inputs as potential P sources. We provide new insights into how a better understanding of the interactions between Po forms, root traits, and rhizosphere microbiomes can help better manage P fertilization, and discuss recent advances in the mobilization and recovery of Po from organic inputs. We then develop proposed strategies in agroecology that could be used to improve Po utilization, specifically by better linking plant traits and Po forms, and developing new cropping systems allowing more efficient Po recycling.